Ethyl Acetate Extraction Atomic Fluorescence Spectrometric Determination of Trace Silver in Seawater - Lu, Jianping; Ni, Huquan; Mao, Chao (Asian Journal of Chemistry, 2013)
A novel method was developed for indirect determination of trace amount of silver in seawater by ethyl acetate extraction-atomic fluorescence spectrometry (AFS). Based upon the complex, formed among Ag+, I– and Hg2+ in 0.2 mol L-1 of nitric acid and extracted by ethyl acetate, the mercury is determined in terms of silver. The effects of extraction conditions and other factors on the determination were investigated. Under the optimum experimental conditions, the results showed that the linearity located in 0-8 μg mL-1 silver, the detection limit was 8.8 ng mL-1 and the relative standard deviation was 1.5-3.5 %. The method was applied to determine the trace amount of silver in seawater with recoveries of 99.6-112.0 %.